2021
DOI: 10.2147/rrtm.s339058
|View full text |Cite
|
Sign up to set email alerts
|

Are Pathogenic Leptospira a Possible Cause of Aseptic Meningitis in Suspected Children in Sudan?

Abstract: Introduction Clinical presentations of leptospirosis are diverse, with meningitis easily confused with other microbial causes. We aimed to investigate the involvement of pathogenic leptospira in the cerebrospinal fluid (CSF) of meningitis-suspected children in Sudan. Methods A total of 153 CSF specimens were collected over 5 months from patients attending a reference pediatric hospital in Omdurman, Sudan. All patients had provisionally been diagnosed with meningitis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The overall clinical, nucleic acids and conventional microbial findings are illustrated in Figure 1 which describes findings from this study alongside findings reported in our other publications. [17,20,21]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall clinical, nucleic acids and conventional microbial findings are illustrated in Figure 1 which describes findings from this study alongside findings reported in our other publications. [17,20,21]…”
Section: Resultsmentioning
confidence: 99%
“…[20] § This number is the sum of 18 cases with level-1 of diagnostic certainty for aseptic meningitis along with 16 cases with laboratory evidence of non-cultivable microbial etiology (further information is presented in our previous publications. [21,22] ‖ Four cases with confirmed HSV-1 and HEV DNA/RNA and 12 cases with other confirmed viral nucleic acids (this information is presented in our previous publication. [21] by PCR initial activation step necessary for HotStarTaq ® DNA Polymerase (Qiagen ® , Hilden, Germany) at 95°C for 10 minutes, then denaturation at 94°C for 15 seconds and combined annealing and extension at 60°C for 60 seconds.…”
Section: Synthesis Of Cdnamentioning
confidence: 98%
See 2 more Smart Citations
“…9 In about 10% of patients infected with pathogenic serovars, the symptoms may progress to fulminant leptospirosis, known as Weil's disease, characterized by multiorgan dysfunction with pulmonary hemorrhage, renal and liver impairment. 10,20 In children the disease is also associated with meningitis 21 and case fatality rates for severe disease range from 10% to 30%. 17,[22][23][24] Studies of bidirectional interactions between Leptospira infection and HIV are scarce worldwide, especially from sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%